Marianne is watching : intelligence, counterintelligence, and the origins of the French surveillance state - Bauer, Deborah (University of Nebraska Press, 2021)
"Deborah Bauer presents the history of French espionage and counterespionage services in the era of their professionalization, arguing that the expansion of surveillance practices reflects a change in understandings of how best to protect the nation"-- Provided by publisher.
Keywords: Intelligence service -- France -- History -- 19th century.; Espionage -- France -- History -- 19th century.; Service des renseignements -- France -- Histoire -- 19e siècle.; Espionnage -- France -- Histoire -- 19e siècle.; HISTORY / Europe / France; Espionage; Intelligence service; France; 1800-1899; History